(untitled) (University of Khartoum Engineering Journal, 2022)
Deficiency of sanitation systems and contaminated surface-runoff in urban and rural communities cause serious environmental problems by deteriorating water quality of surface and ground water. The aim of this study is to evaluate the degree of water pollution (surface and ground) in Khartoum State, to determine the symptoms of the environmental problems and to suggest some solutions. The study included analysis of 24 surface water samples, in two seasons, from the River Nile, the Blue Nile, and the White Nile. High values of biochemical oxygen demand (251 mg/l, 210 mg/l) in two locations indicate that there are pollution problems, values of chemical oxygen demand, and biological tests emphasized the occurrence of pollution loads. Questionnaires analysis, which has been distributed as part of this study, showed that the use of septic tanks with soakaway wells (shallow wells receiving septic tank effluents) forms about 21% of sanitation systems in Khartoum, 73% of Khartoum population use pit-latrines, about 1.5% only served by sewerage system, and the rest percentage use other poor sanitation system. Samples were collected from nine soakaway wells receiving septic tanks effluents. Average values of ammonia concentration about 27 mg/l indicate that the quality of ground water aquifers may be threatened by chemical pollution load. As ammonia will be oxidized to nitrate through time as effluents seep through cracks and fissures of soil strata to deep aquifers. To improve the situation of sanitation systems, some Mitigation measures such as adopting ventilated improved pit latrines, erecting small bore sewers and extending the coverage of conventional gravity sewers have been suggested. Upgrading the systems by 50%, 25% and 25%, respectively, will improve the environment in Khartoum state. A total cost estimate of abort 1518 million US is required for upgrading sanitation systems in Khartoum state within three phases in a plan extending to 2030.